Design Constraint Systems - A Generative Approach to Architecture. (March 2013) - Bollmann, Dietrich; Bonfiglio, Alvaro
Generative Architectural Design permits the automatic (or semiautomatic) generation of architectural objects for a wide range of applications, from archaeological research and reconstruction to digital sketching. In this paper the authors introduce design constraint systems (DCS), their approach to the generation of architectural design with the help of a simple example: The development of the necessary formalisms to generate a family of architectural designs, i.e. simple houses and pagodas. After explaining the formal system the authors introduce an approach for the generation of complex form based on the application of transformations and distortions. Architecture is bound by the constraints of physical reality: Gravitation and the properties of the used materials define the limits in which architectural design is possible. With the recent development of new materials and construction methods however, the ways in which form and physics go together get more complicated. As a result, the shapes of architecture gain more liberty, and more and more complex shapes and structures become possible. While these advances allow for new ways of architectural expression, they also make the design process much more challenging. For this reason new tools are necessary for making this complexity manageable for the architect and enable her to play and experiment with the new possibilities of complex shapes and structures. Design constraint systems can be used as tool for experimentation with complex form. Therefore, the authors dedicate the final part of this paper to a concise delineation of an approach for the generation of complex and irregular shapes and structures. While the examples used are simple, they give an idea of the generality of design constraint systems: By using a two-component approach to the generation of designs (the first component describes the abstract structure of the modelled objects while the second component interprets the structure and generates the actual geometric forms) and allowing the user to adjust both components freely, it can be adapted to all kind of different architectural styles, from historical to contemporary architecture.